Debates on latinamerican structuralism and neo-structuralism: placing the State at the forefront of the analysis (Estudios Sociales, 2020)
Starting from recognizing the lack of consideration of the analytical restrictions related to the role of the state in ECLAC’s development proposal, the article revalues ​​the specificities of the configuration and involvement practices of Latin American states in order to understand their inability to direct the accumulative pattern towards a structural transformation. In this sense, the practices deployed on and from the states during the period of import substitution industrialization are analysed, showing how they finally acted, on the one hand, in a functional way to the recreation of the obstacles that gave specificity to the pattern of peripheral accumulation, and, on the other hand, configuring the own weakness of the states to confront the consequent transformations of capitalism after 1970.
Keywords: State; development; Latin America; ECLAC